Caracterização para fins industrial dos amidos nativo e modificados extraídos de amêndoas de sementes de manga, variedade Tommy Atkins - Mendes, Marianne Louise Marinho (2011)
After the industrial processing of mango, stone and shell are usually discarded without its proper use. The objective of this research was to study the native and modified starches (by oxidation, acidification, succinylation and acetylation) of mango kernels seeds, variety Tommy Atkins, comparing their properties for possible use in the food industry. The native starch showed 71.56 % starch, 7.30 % lipids and 5.6 % proteins. The percentage of carbonyl and carboxyl groups present in oxidized starch were 0.05 and 0.09 respectively. The degree of substitution was 0.006 to the succynilated starch and 0.025 to the acetylated starch. It was observed that the chemical modification did not alter the shape and form of starch granules and these demonstrated shapes ranging from oval to ellipsoid, large diameter from 5.52 to 29.8 μm and smaller diameter from 4.17 to 22.55 μm. The starch that revealed the highest swelling power in relation to temperature was the acetylated one (19.994 g.g-1) at 85oC. The acidified starch exhibited the highest solubility according to the temperature (48.03 %). Succynilated starch presented the highest swelling power varying the pH, 13.615 g.g-1 at pH 4. This same starch revealed the highest solubility according to pH, 16.60% at pH 12. Oxidized starch demonstrated the greatest water absorption capacity (105.97 g.100g-1) and the lowest oil absorption capacity (50.74 g.100g-1). The paste of native starch exposed the greatest light transmittance (13.45 %). Concerning to the paste properties, oxidized starch had higher values for all the parameters analyzed: peak viscosity (3071.50 cP), minimum viscosity (1088.50 cP), breakdown (1983.00 cP), final viscosity (4853.50 cP), setback (3765.00 cP) and paste temperature (79.70 oC). The properties found for the starch of this research indicate that they have possible uses in the food industry.